2020
DOI: 10.3892/etm.2020.9499
|View full text |Cite
|
Sign up to set email alerts
|

miR‑126‑5p regulates H9c2 cell proliferation and apoptosis under hypoxic conditions by targeting IL‑17A

Abstract: Accumulating evidence has indicated that microRNAs (miRNAs/miRs) regulate the occurrence and development of various diseases, including diabetes, osteoporosis and cardiovascular conditions. However, the role of miRNAs in acute myocardial infarction (AMI) is not completely understood. The present study aimed to evaluate the therapeutic efficacy and mechanisms underlying the effects of miR-126-5p on H9c2 cell proliferation and apoptosis by targeting interleukin (IL)-17A. A total of 40 patients with AMI and 40 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The findings are consistent with our previous reports that hypoxia with concurrent acidosis, but not hypoxia alone confers lethal cardiac myocyte injury through BH3-only pathways [9][10][11]35,36,50]. The results are also consistent with our previous report, and that of others that miR-126, while generally considered to be endothelial-specific is induced by hypoxia in non-endothelial cells including cardiac myocytes and regulates pro-survival kinases and inflammatory cytokines [32,51]. Acidosis appears to be the critical regulator of miR-126 expression in this model and the implications of the studies extend beyond those of ischemic cardiac injury to other conditions of acidosis including rapidly growing solid tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings are consistent with our previous reports that hypoxia with concurrent acidosis, but not hypoxia alone confers lethal cardiac myocyte injury through BH3-only pathways [9][10][11]35,36,50]. The results are also consistent with our previous report, and that of others that miR-126, while generally considered to be endothelial-specific is induced by hypoxia in non-endothelial cells including cardiac myocytes and regulates pro-survival kinases and inflammatory cytokines [32,51]. Acidosis appears to be the critical regulator of miR-126 expression in this model and the implications of the studies extend beyond those of ischemic cardiac injury to other conditions of acidosis including rapidly growing solid tumors.…”
Section: Discussionsupporting
confidence: 93%
“…MiR-126 is enriched in endothelial cells (EC) and EC progenitors, and has been assigned essential roles in cardiac developmental as well as in the recovery of the heart from injury by activating survival kinases ERK1/2 and Akt and increasing proangiogenic signaling [29][30][31]. Roles for mirR-126 have also been described in the regulation of cardiac myocyte proliferation and inflammation, including Interleukins in non-endothelial H 9 c 2 cells [32]. Aberrant expression of miR-126 associated with vascular pathologies including but not limited to cancers, diabetes and ocular disease has revealed roles in a range of biological processes including apoptosis, autophagy, pathological angiogenesis, cell migration and proliferation [33,34].…”
Section: Article Info Abstractmentioning
confidence: 99%
“…Although miR-126 has been widely studied in the context of cellular hypoxia [22][23][24][25][26][27], its role in ECs subjected to chronic ischemic and/or acidotic conditions is relatively unexplored. HIF-1α has been shown to induce the miR-126 expression in a number of cell types including cultured human umbilical vein endothelial cells, and other studies have described positive feedback loop regulation between HIF-1α and miR-126 [26,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis refers to an active, programmed process of autonomous cellular dismantling, and necrosis is described as unplanned cell death resulting from environmental perturbations in the inflammatory process [ 54 ]. A previous in vitro study indicated that miR-126-5p may regulate H9c2 cell viability and apoptosis by targeting IL-17A under hypoxic conditions [ 55 ]. Another study revealed that overexpressing miR-140-3p may exert cytoprotective effects by alleviating inflammation and oxidative stress and reducing cell apoptosis in OGD/R [ 56 ].…”
Section: Discussionmentioning
confidence: 99%